PENGARUH INTEGRITAS DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT JASAMARGA TOLLROAD OPERATOR CABANG SURABAYA – GEMPOL WILAYAH DUPAK RAYA SURABAYA : Keywords: Integrity, Motivation, Job Performance - Yusuf, Farizah (GEMA EKONOMI, 2021)
This research is aimed to reveal: (1) the influence of integrity on job performance of employees in the PT Jasamarga Tollroad Operator Surabaya – Gempol branch Dupak Raya section, (2) the influene of motivation on job performance of employees in the PT Jasamarga Tollroad Operator Surabaya – Gempol branch Dupak Raya section, and (3) the influence of integrity and motivation on job performance of employees in the PT Jasamarga Tollroad Operator Surabaya – Gempol branch Dupak Raya section. This research was survey research. The population was all employees who worked for PT Jasamarga Tollroad Operator, Surabaya – Gempol branch Dupak Raya section and 70 of them were used as the samples. The data were collected using questionnaire whose validity and reliability had been tested. The data analysis technique of the research was multiple regressions. The results of the research showed that: (1) Integrity significantly influential the job performance with 2,586 regression value and 0,012 significance level; (2) the motivation significantly influential the job performance with 2,109 regression value and 0,039 significance level; and (3) integrity and motivation significantly influential the job performance with 0,005 regression level which was less than 0,05 (p<0,05). The big influence of integrity and motivation showed 12% of job performance variable while the rest which was 88% was shown by other variables outside this research.